Structural organization of the 19S proteasome lid: insights from MS of intact complexes. - Sharon, M; Taverner, T; Ambroggio, X; Deshaies, R; Robinson, C (2006)
The 26S proteasome contains a 19S regulatory particle that selects and unfolds ubiquitinated substrates for degradation in the 20S catalytic particle. To date there are no high-resolution structures of the 19S assembly, nor of the lid or base subcomplexes that constitute the 19S. Mass spectra of the intact lid complex from Saccharomyces cerevisiae show that eight of the nine subunits are present stoichiometrically and that a stable tetrameric subcomplex forms in solution. Application of tandem mass spectrometry to the intact lid complex reveals the subunit architecture, while the coupling of a cross-linking approach identifies further interaction partners. Taking together our results with previous analyses we are able to construct a comprehensive interaction map. In summary, our findings allow us to identify a scaffold for the assembly of the particle and to propose a regulatory mechanism that prevents exposure of the active site until assembly is complete. More generally, the results highlight the potential of mass spectrometry to add crucial insight into the structural organization of an endogenous, wild-type complex.